Performance improvement of MAC layer in terms of reverse direction transmission based on IEEE 802.11n - Milad, Ali Ahmad (2015)
Medium access control (MAC) layer is one of the most prominent topics in the area of wireless networks. MAC protocols play a big role in improving the performance of wireless networks, and there are many challenges that have been addressed by the researchers to improve the performance of MAC layer in the family of IEEE 802.11. The physical data rate in IEEE 802.11n may reach 600 Mbps, this high data rate does not necessary transform into good performance efficiency, since the overhead at the MAC layer signifies that by augmenting PHY rates the effectiveness is automatically reduced. Therefore, the main objective of next generation wireless local area networks (WLANs) IEEE 802.11n is to achieve high throughput and able to support some applications such as TCP 100 Mbps and HDTV 20 Mbps and less delay. To mitigate the overhead and increase the MAC efficiency for IEEE 802.11n, one of the key enhancements at MAC layer in IEEE 802.11n is a reverse direction transmission. Reverse direction transmission mainly aims to accurately exchange the data between two devices, and does not support error recovery and correction; it drops the entire erroneous frame even though only a single bit error exists in the frame and then causes a retransmission overhead. Thus, two new schemes called (RD-SFF) Reverse Direction Single Frame Fragmentation and (RD-MFF) Reverse Direction Multi Frame Fragmentation are proposed in this study. The RD-SFF role is to aggregate the packets only into large frame, while RD-MFF aggregate both packets and frames into larger frame, then divided each data frame in both directions into subframes, Then it sends each subframe over reverse direction transmission. During the transmission, only the corrupted subframes need to be retransmited if an error occured, instead of the whole frame. Fragmentation method is also examined whereby the packets which are longer when compared to a threshold are split into fragments prior to being combined. The system is examined by simulation using NS-2. The simulation results show that the RD-SFF scheme significantly improves the performance over reverse direction transmission with single data frame up to 100%. In addition, the RD-MFF scheme improvers the performance over reverse direction transmission with multi data frames up to 44% based on network condition. These results show the benefits of fragmentation method in retransmission overhead and erroneous transmission. The results obtained by ON/OFF scheme takes into account the channel condition to show the benefits of our adaptive scheme in both ideal as well as erroneous networks. In conclusion, this research has achieved its stated objective of mitigation the overhead and increase the MAC efficiency for IEEE 802.11n. Additionally, the proposed schemes show a significant improvement over the reverse direction in changing network conditions to the current network state.